Shear bond strength of metallic brackets photo-activated with light-emitting diode (LED) at different exposure times - Emanuel Braga Rêgo; Fábio Lourenço Romano (University of São Paulo, 2007)
The purpose of this study was to compare the shear bond strength of orthodontic metallic brackets photo-activated with two different light-curing sources at different exposure times: halogen light (XL 1500, 3M ESPE) and LED light (Ortholux, 3M Unitek). Sixty bovine permanent lower incisors were inserted into PVC tubes containing plaster. The buccal surfaces were cleaned with pumice and water, and then etched with 37% phosphoric acid gel. The XT Primer bonding agent (3M Unitek) was applied to the enamel surfaces and the metallic pre-coated brackets (Transbond APC II system, 3M Unitek) were attached to upper central incisors. The teeth were randomly divided into four groups (n=15). In Group I (Control), halogen light was used for 40 seconds, while in Groups II, III, and IV were light-cured with LED light unit for 40, 10, and 5 seconds, respectively. The teeth were stored in distilled water at 37°C for 24 hours. The brackets were submitted to shear bond strength test in universal testing machine (Instron) at a crosshead speed of 0.5 mm/minute. Shear bond strength means (MPa) were 4.87 for Group I; 5.89 for Group II; 4.83 for Group III, and 4.39 for Group IV. Tukey's test detected no statistically significant differences among the groups regarding the shear bond strength (p>0.05). Neither of the types of light-curing sources or exposure times influenced the shear bond strength of metallic brackets.